2021
DOI: 10.1080/17565529.2021.1924109
|View full text |Cite
|
Sign up to set email alerts
|

Role clarification for local institutions: a missing link in multi-level adaptation planning? Insights from a multiple case study in Botswana

Abstract: The meaningful engagement of community-based actors in climate change adaptation planning is crucial for effective plans, but achieving it is an ongoing challenge, even with participatory methods. In this paper we explore very different approach, using shared-values crystallization as a pre-process to standard vulnerability risk assessments (VRAs), which recently reported significant impacts on plans produced. We posit this could be due to learning via changed local perceptions of roles, and we use multiple-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…WeValue was originally co-designed using research-through-design methods [ 37 , 38 ] with civil society groups to crystallize their tacit shared values (for example to provide performance indicators which held high face-validity [ 39 ]. It was then found to incidentally produce some types of Transformative Learning [ 40 ] especially when used with participants who had a background with common in-situ experiences [ 41 ] in which case it was named WeValue InSitu (WVIS) to indicate the boundary within which the process proceeded. One strand of later studies [ 25 , 28 ], focused on detailed examinations of the TL outcomes of the standard WVIS approach, and confirmed that it routinely led to durable transformations of behaviours with respect to formal definitions of [ 27 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…WeValue was originally co-designed using research-through-design methods [ 37 , 38 ] with civil society groups to crystallize their tacit shared values (for example to provide performance indicators which held high face-validity [ 39 ]. It was then found to incidentally produce some types of Transformative Learning [ 40 ] especially when used with participants who had a background with common in-situ experiences [ 41 ] in which case it was named WeValue InSitu (WVIS) to indicate the boundary within which the process proceeded. One strand of later studies [ 25 , 28 ], focused on detailed examinations of the TL outcomes of the standard WVIS approach, and confirmed that it routinely led to durable transformations of behaviours with respect to formal definitions of [ 27 , 42 ].…”
Section: Introductionmentioning
confidence: 99%